Fenotipik varietas kedelai pada jarak tanam berbeda yang ditumpangsarikan dengan tanaman jagung - Suyamto Suyamto; Gatut Wahyu Anggoro Susanto; Pratanti Haksiwi Putri (Fakultas Pertanian Universitas Yudharta Pasuruan, 2021)
The dual system planting aims to utilize existing resources so that they can be more efficient. The research design used separate plots repeated three times. The main plot consisted of soybean spacing of 40 cm x 10 cm (1 plant per hole) (JT-1), 40 cm x 15 cm (2 plants per hole) (JT-2) and 40 cm x 20 cm (2 plants per hole). Lubang) (JT-3), a subplot consisting of 11 varieties of soybeans. Soybeans were planted in 3 rows along 5 m which were intercropped with maize varieties Lamuru (120-50 cm) x 20 cm, (1 plant/hole) at IP2TP Muneng, Probolinggo Regency, East Java in MK II 2018. The results showed that the varieties "Dena 1" and "Deja 1" matched the intercropping pattern with maize, which were able to achieve seed productivity of 2.17 t/ha and 2.13 t/ha, respectively. Argomulyo and Anjasmoro varieties in JT-1, Deja 1 on JT-2, and Deja 2 on JT-3 were able to achieve seed productivity of up to 2.0 t / ha. The phenotypic weight of seeds per plant and the number of filled pods were two components that contributed greatly to the increase in seed productivity. Dena 1 varieties correspond to JT1 and JT-2 treatments, while Deja 1 varieties correspond to JT-3 treatments. The phenotypic weight of 100 seeds, plant height, and the number of branches contributed little to the increase in seed productivity.